The Analysis of Coalition Parties´ Election Programme Fulfillment: Czech Case Study - Kuba, Ondřej; Stejskal, Jan (Diamond Scientific Publication, 2019)
In multi-party democratic systems, where there is no absolute majority, the political parties are forced to cooperate. The cooperation is built on negotiations that result in several side effects including also concessions and compromises in the program. This analysis focused on the fulfillment of the coalition party promises in the Czech Republic, specifically on Prime Minister Bohuslav Sobotka´s government. The input data of the research consisted of a prepared set of testable political promises from the pre-election programs of selected political parties. The promises were compared with the contents of the coalition agreement, the government's policy statement. It was found that coalition political parties selected by the government within the framework of coalition cooperation managed to enforce approximately 36 % of their election promises. At the program level, 24 % of promises were enforced. In areas that increase the personal budget of voters, government political parties have pushed 76 % of promises. Regardless of their cooperation, they made approx. 52 % of the election promises during the parliamentary term. The dominant party of the government was the CSSD.
Analýza plnění volebního programu koaličních stran: Česká republika
Keywords: coalitions; government; public choice; pledges; elections; koalice; vláda; veřejná volba; sliby; volby